2011
DOI: 10.1055/s-0030-1270703
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Changes Associated with Hemodynamically Significant Myocardial Bridges in Sudden Cardiac Death

Abstract: Hemodynamically significant myocardial bridging can be discovered during heart dissection by analyzing a series of morphological markers (width, distribution of atherosclerosis, distal hypoplasia). Our study showed that MB was associated with increased myocardial fibrosis and edema, both of which have an increased risk of electrical instability. Compared to non-hemodynamically significant myocardial bridging, HSMB shows a distinct histological pattern, with increased myocardial fibrosis and edema. The main cau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
29
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 45 publications
0
29
0
Order By: Relevance
“…Various studies suggested that, to have hemodynamic significance, a MB has to have some particular morphological characteristics (especially length and thickness) . Our study showed that a “typical” myocardial bridge has around 19 mm in length and 2.5 mm in thickness, values that can be considered hemodynamically significant .…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…Various studies suggested that, to have hemodynamic significance, a MB has to have some particular morphological characteristics (especially length and thickness) . Our study showed that a “typical” myocardial bridge has around 19 mm in length and 2.5 mm in thickness, values that can be considered hemodynamically significant .…”
Section: Discussionmentioning
confidence: 49%
“…Most authors suggested that MB is a benign condition, even though some found a positive correlation with myocardial ischemia (4-7), AMI (8), or other major adverse cardiac events (9,10). In forensic autopsies, it is sometimes considered a cause of sudden death and is often reported as such in scientific articles, especially in association with other congenital cardiac or coronary anomalies (11)(12)(13)(14)(15)(16)(17)(18)(19)(20). It is considered an inborn anomaly, being found in studies on human fetuses (21), and it appears to reflect particular developmental processes within the heart (22).…”
mentioning
confidence: 99%
“…The recent histopathologic studies indicated that myocardial fibrosis and interstitial edema can occur in the area of MB (26). Similarly, in a report by Hostiuc et al (27), significant myocardial fibrosis and interstitial edema were demonstrated in the bridged segment in patients who had sudden cardiac death. Death in these patients was emphasized to be related to increased electrical instability due to myocardial fibrosis.…”
Section: Discussionmentioning
confidence: 70%
“…At present the exact mechanism of MCA and distal segment of the bridged artery usually free from atherosclerosis remains unclear. The mechanisms may include decreased blood flow and volume, increased endothelial shear stress and reduced bioavailability of nitric oxide and endothelin-1 (15,31). Although the protective effect of MB exists, the diastolic narrow rates ≥30% of MCAs in 8 patients, ulcer-like lesion in MCA in 1 patient and 36 lesions located distally to MBs were detected.…”
Section: Discussionmentioning
confidence: 99%